1986
DOI: 10.1002/bjs.1800730316
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin once daily compared with conventional low-dose heparin twice daily. A prospective double-blind multicentre trial on prevention of postoperative thrombosis

Abstract: In a randomized, prospective, double-blind multicentre trial, the effect of conventional low-dose heparin 5000 units twice daily, was compared with that of a low molecular weight heparin fragment (4000-5000) 5000 anti-factor Xa units once daily. Four hundred and thirty-two patients fulfilled the inclusion criteria and were analysed for development of deep vein thrombosis (125I-labelled fibrinogen test) and haemorrhagic complications. Thrombosis occurred in a 4.3 per cent of patients in the low-dose heparin gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 21 publications
1
63
2
3
Order By: Relevance
“…The incidence of DVT (clinically evident) observed in our population is substantially lower than that reported in the literature using various LMWHs [18, 19, 20, 21]. Besides the specifically used LMWHs, this can be attributed to several different factors.…”
Section: Discussioncontrasting
confidence: 50%
“…The incidence of DVT (clinically evident) observed in our population is substantially lower than that reported in the literature using various LMWHs [18, 19, 20, 21]. Besides the specifically used LMWHs, this can be attributed to several different factors.…”
Section: Discussioncontrasting
confidence: 50%
“…Two original studies in 1986 reported that prophylaxis with LMWH in elective major abdominal surgery is as effective as UFH in preventing postoperative thrombosis 10,11 . Bergqvist et al 10 reported a double-blind *No statistical evaluation published in original paper; **all patients also received dihydroergotamine; †all patients wore elastic compression stockings; ‡trend only as study was stopped prematurely.…”
Section: General Abdominal Surgerymentioning
confidence: 99%
“…Recently, several wellconducted, randomized, clinical trials have clearly established that LMWHs adminis tered once daily are as effective as standard heparin given twice daily in preventing post operative thrombosis in general surgery [14][15][16][17]. However, increased bleeding was ob served in two trials [14,16] and correlated with a high plasma anti-Xa activity. The question arises whether LMWHs given at a fixed-dose are effective and safe in prevent ing postoperative DVT in elective hip sur gery.…”
Section: Discussionmentioning
confidence: 99%